Pengelolaan Keuangan dan Administrasi Usaha bagi Pengelola Pariwisata - Metha Dwi Apriyanti; Lena Erdawati; Dede Sunaryo; Andi Kusuma Negara (JURNAL PENGABDIAN MANAJEMEN, 2025)
Warnasari Village in Cileunca District, Bandung Regency, is a pioneering tourism village with promising natural and cultural tourism potential. However, tourism-related MSME actors in the village face challenges in financial management and business administration. This community service activity aims to improve the capacity of MSME managers through training and mentoring in financial management and business administration. The partners of this program are 124 MSME actors in Warnasari Village. The methods used include participatory training, hands-on simulation, and advocacy based on local needs. The results of the program indicate a significant improvement in participants' understanding and skills, as shown by increased post-test scores in both financial and administrative management aspects. This activity also raised awareness about the importance of structured and professional business documentation. These findings highlight that practical training based on real community needs can enhance competitiveness and sustainability in tourism village enterprises. Such capacity-building efforts are crucial to be replicated in other tourism village areas.